Bridging the Digital Divide: Empowering Coastal Women through Public Sector Innovation - Arif Ginanjar; Toddy Aditya; Sukma Aditya Ramadhan (Dinasti Publisher, 2025)
Public sector innovation holds transformative potential in addressing digital inequality, particularly among marginalized women in coastal regions. However, the gender digital divide remains persistent due to socio-cultural and infrastructural barriers. This study examines how digital literacy, diffusion of innovation, and digital infrastructure affect the digital divide among coastal women in Tangerang Regency, Indonesia. Using a quantitative approach and Structural Equation Modeling-Partial Least Squares (SEM-PLS), data were collected from 400 respondents and analyzed to assess the impact of key constructs on digital inequality. The findings reveal that all three factors significantly reduce the digital divide, with digital literacy being the strongest determinant. The study also affirms the relevance of the Diffusion of Innovation Theory in understanding digital adoption patterns among underserved populations. A multifaceted strategy involving capacity-building, infrastructure development, and inclusive innovation diffusion is essential to bridge the gender digital divide. The research provides empirical insights for policymakers, emphasizing the need for community-centered and gender-responsive digital policies.